Diversiteit in het hoger onderwijs: van theoretisch kader naar praktijkgerichte verandering - Pulinx, Reinhilde 1976-; Schrooten, Mieke 1978-; Emmers, Elke (Brussel ASP Academic & Scientific Publishers, 2021)
Diversity is a social reality, yet this diversity is still too absent from higher education. Universities and colleges are aware of this contrast, but how do we bring more diversity into higher education, and what exactly are we talking about? It's about diversity in the student population, but also in the workforce. It's about accessibility for students with disabilities, dealing with multilingualism and making room for non-Western perspectives in degree programs. It is about paying attention to individual needs and requirements of students and staff and creating an environment where everyone finds their place. It is about providing inclusive and qualitative higher education. In this book, we let diverse voices from Flanders and the Netherlands speak and offer both practical examples and theoretical reflections. The book appeals to all actors within higher education - teachers, teacher trainers, students and support staff - and presents a future-oriented framework for working on diversity in higher education.(Translated with DeepL.com)
Keywords: Education